2022
DOI: 10.1007/s12553-021-00627-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving safety in dental practices during the COVID-19 pandemic

Abstract: Coronavirus disease 2019 (COVID-19) is caused by a novel coronavirus, known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It originated from the Chinese city of Wuhan and very quickly became a challenging public health problem. On 11 March 2020, the World Health Organization termed this potentially deadly disease a pandemic due to its rapid spread in various parts of the world, giving rise to international health emergencies. This virus is transmitted from human to human in the form of respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…As of 8 June 2022, there have been 530,896,347 confirmed COVID-19 cases, including 6,301,020 deaths, as reported by the WHO [ 72 ]. Further, recently identified, highly transmissible, and evolving variants—such as B.1.1.7 (202012/01), B.1.351 (501Y.V2), and P.1.—continue to draw the attention of health authorities [ 73 , 74 ]. This rise in cases could be the fallout of the relaxation of public health measures, such as the reluctance to adhere to preventive social measures, including social distancing, avoiding crowds, wearing of masks, and hand hygiene [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…As of 8 June 2022, there have been 530,896,347 confirmed COVID-19 cases, including 6,301,020 deaths, as reported by the WHO [ 72 ]. Further, recently identified, highly transmissible, and evolving variants—such as B.1.1.7 (202012/01), B.1.351 (501Y.V2), and P.1.—continue to draw the attention of health authorities [ 73 , 74 ]. This rise in cases could be the fallout of the relaxation of public health measures, such as the reluctance to adhere to preventive social measures, including social distancing, avoiding crowds, wearing of masks, and hand hygiene [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…A suitable toothbrush should be used for children with erupted teeth. For those without erupted teeth, the gingival mucosa should be washed with sterile gauze dipped in a proper antiseptic solution (6).…”
Section: Preventive Methods Of Covid-19 For Dentistsmentioning
confidence: 99%
“…A study by Benahmed et al (6) showed that only a few of the patients who visited outpatient departments during the pandemic required serious pain management. Marui et al (7) reported that during the pandemic, most patients reported abscesses and periapical lesions.…”
Section: Effect Of Covid-19 On Dental Carementioning
confidence: 99%
“…Several disinfectants and cleaning solutions are currently available for microbiologic control at the dental office, including viruses. However, most of them are not entirely innocuous for humans, dental instruments, materials, and the environment and are not fully effective in controlling the virus dissemination [10,11]. From this basis, the use of electrolyzed water has brought recent attention due to its bactericidal and virucidal activities and less detrimental effects on biological tissues, skin, and mucosa [12].…”
mentioning
confidence: 99%